SCHOOL FACTORS THAT INFLUENCE FEMALE LEARNERS’ DEVELOPMENT OF A NEGATIVE SELF-CONCEPT IN MATHEMATICS: THE CASE OF A RURAL HIGH SCHOOL IN CENTRAL ZAMBIA - Nachivula, Chongo; Munsaka, Ecloss (New Voices in Psychology, 2016)
The study was aimed at ascertaining school factors, which influence the development of negative mathematics self-concept in female learners. The study used a case study approach. A sample comprising 7 grade 11 female learners with low mathematics self-concept from Kalale (pseudonym) Girls’ Secondary School, situated in a rural area of central Zambia, was purposively selected. The Rosenberg self-concept scale was used to identify learners with low mathematics self-concept. In-depth face-to-face interviews and a focus group discussion were conducted with the participants. Data were analysed using the Interpretative Phenomenological Analysis (IPA) method. Findings revealed that there were six school factors that influenced the female learners to have a negative self-concept in mathematics. These factors are: bad personality attitudes of mathematics teachers; lack of support from teachers; teachers’ mathematics related gender stereotypes; few female mathematics teachers; lack of adequate and consistent guidance and counselling programs in the school; and poor organisation of the mathematics club in the school.